Automatic window curtain (AWC) / Musyrifah Arbi ...[et al.] - Arbi, Musyrifah; Mohd. Nasir, Nuramni; Abdul Halim, Nur Syuhada Fitriah; Bashah, Siti Hajar (2016)
After observation of existing window curtain, the team had decided to choose a product that is easier for people to open and close the curtain.. The product is Automatic Window Curtain (AWC). Nowadays, people are getting busy with daily activity at the office, they do not have much time to tidy up their house and sometimes they even forgot to open up their curtain in the morning before leaving for works. Therefore, this product is suitable for every house that have a window.